Quantifying student satisfaction with technology-enhanced textbooks in the Japanese university context - Daniel James Mills; Daniel Olsson (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2020)
Thirty-three students used their personal mobile devices to access digital media in a paper-based textbook containing Quick Response (QR) codes. The students worked in small groups with minimal intervention from the course instructor to participate in activities and complete assignments. Information regarding student satisfaction with the course, as well as their perceptions of the benefits and disadvantages of the instructional method employed, were gathered through a questionnaire and a reflective writing activity. The results indicated that overall satisfaction was high (M = 3.38), especially regarding the role of the instructor (M = 3.35) and interaction (M = 3.35). However, participants indicated a lower level of satisfaction with the materials (M = 2.89). Further inquiry revealed that dissatisfaction with the course materials was due to the lack of a stable Wi-Fi connection at the university rather than the design or content of the textbooks.